The power of process auditing [ [the reality video] - Ferguson, Murray (Nicholas and Smith Pty, 2005)
"The video is a 'reality' style program which follows an internal auditor conducting a typical process audit. The video shows how he conducts a process audit, the approach he takes and the skills he uses to uncover important issues. The process being audited is the filling and labelling of gas cylinders and, in particular, a medical gas product known as Entonox. Through his findings, the auditor develops a scenario for the potential for cylinders to be incorrectly labeled and to be delivered to customers. This scenario is presented to management and discussed in terms of its level of risk and possible solutions which should be further explored"--Study guide